STUDY OF THE RELIABILITY OF IRRIGATION CANALS AND THEIR PIPELINE WATER TRANSFER FACILITY - E. S. Nabiyev; Sh. X. Boymatov; Sh. A. Raximov; Sh. X. Samiyeva (Academia Science Repository, 2023)
The reliability of an object should be understood as its non-measurable description. However, it can be estimated based on the experience of using this or a similar object, using methods of mathematical statistics and probability theory.